Nutrional Counseling and “Sukahitu “Cookies Making Demonstration: An Alternative to Promote Blood Hemoglobin Increase in Women of Reproductive Age and Pregnant Women in Belawan II Village, Medan Belawan District - Oppusunggu, Riris (Journal of Saintech Transfer, 2024)
Anemia poses a significant risk for women of reproductive age and pregnant women, impacting both their health and the quality of future generations. This condition can adversely affect the growth and development of the fetus, leading to potential complications during pregnancy and childbirth. In severe cases, it may even result in maternal and newborn mortality. The purpose of this community service activity was to enhance the knowledge of women of reproductive age and pregnant women through nutritional counseling and demonstrations on making "sukahitu" cookies, which serve as an alternative for increasing blood hemoglobin levels. “Sukahitu” cookies, made from katuk (Sauropus androgynus) leaf flour and mung bean flour, were provided daily for 30 days to 35 women of reproductive age and pregnant women in Belawan II Village, Medan Belawan District. Knowledge regarding intake, anemia, and hemoglobin was measured before (pretest) and after the intervention (posttest). The results of the activity indicate that the average pretest score is 77.1%, and the posttest score is 91.4%. There is an average increase of 14.28% in knowledge about anemia. It is recommended to regularly conduct nutrition and anemia counseling for women of reproductive age and pregnant women, along with providing hemoglobin-rich foods like “sukahitu” cookies to effectively prevent anemia.